Evaluating the presentation of new vocabulary items in Malaysian form three English language textbook - Mat Hussin, Nur Izyan Syamimi; Hossein, Vahid Nimehchisalem; Kalajahi, Seyed Ali Rezvani; Yunus, Nurafazeera (Malaysian Association of Modern Languages, 2016)
Learners in Malaysia usually face difficulties in acquiring their four skills: listening, speaking, reading and writing in English language because of their limited vocabulary knowledge. In order to solve the problem, effective vocabulary learning should be given serious attention. This study aimed to evaluate the presentation of new vocabulary items in the Form Three English language textbook used in Secondary Schools in Malaysia. A group of purposively selected teachers (n = 5) used a checklist to evaluate the presentation of vocabulary items in the textbook. The findings showed that the textbook is weak in vocabulary presentation. It was found that no specific method was followed to teach the new vocabulary. There was no index of the new vocabulary at the end of the textbook. The results have implications for the learners, English language teachers as well as textbook developers. The findings are also expected to provide guidance to teachers for improving their pedagogical practices in teaching vocabulary and to compensate for the weaknesses of the presentation of vocabulary in the textbook.